Investor sentiment and its role in asset pricing: An empirical study for India. Issue 2 (June 2019) - Pandey, Piyush; Sehgal, Sanjay
Abstract: In this paper, we experiment with the construction of alternative investor sentiment indices. Further, we evaluate the role of the sentiment-based factor in asset pricing to explain prominent equity market anomalies such as size, value, and price momentum for India. Based on the findings, we confirm that our Composite Sentiment index leads other sentiment indices currently in vogue in investment literature. The asset pricing models, including the more recent Fama French 5 factor model, are not fully able to explain the small firm effect which is captured by our sentiment-based factor which seems to proxy for the price over-reactions.